The Islamic Education Perspective on Proactive Legal Protection and Hifz a-Mal: Highlighting the Rights of Domestic Workers in Medan - Suria Ningsih; Nurhayati Nurhayati; Dhiauddin Tanjung (Edukasi Islami: Jurnal Pendidikan Islam, 2022)
At the very minimum, every worker's rights include a decent salary, reasonable working hours, and access to social security. All workers, including domestic workers, are included in the worker in consideration (PRT). In general, metropolitan regions, including Medan, are areas that within the "family circle" use the services of domestic workers. As a result, the findings of this study will shed light on the protection of domestic workers' rights in the city of Medan. Islamic education can provide a framework for understanding the human rights of domestic workers and their need for protection. It can also serve to raise awareness of the challenges domestic workers face and how to best protect their rights. Islamic law stresses the importance of justice and fairness, and this can be used to inform the way in which domestic workers are treated. This article analyzes the problem using the Legal Protection and Hifz al-Mal evaluations. This is empirical legal research (sociological); data was collected in the field through interviews and observations. The findings of the study demonstrate that the protection of domestic workers' rights in Medan City is not being implemented, and this problem is caused by a variety of factors, the most significant of which is domestic workers' "ignorance" of their rights at work. As a result, from the standpoint of hifz al-mal, the working relationship between domestic workers and their employers is not in conformity with maqashid al-shariah, because domestic workers do not receive al-daruriah-level salaries. As a result, proactive legal protection is required so that domestic employees can exercise their rights. Proactive legal protection entails involving domestic workers in self-determination; at the very least, domestic workers must be consulted (deliberated) in developing a legal framework that will protect them, so that domestic workers are automatically informed of their legal rights while working.